Necessary but not Sufficient: Literacy Pedagogies for Changing Times - O'Mara, Joanne; Auld, Glenn; Wood, Narelle (Language and Literacy / Langue et littératie, 2021)
This paper argues the case for expansive and inclusive models of literacy pedagogy that can be applied to curriculua more generally. Literacy pedagogy in Australia has benefitted from using Freebody and Luke's (1990) Four Roles of the Reader Model. We analyse the Paul Kelly song video, Sleep, Australia, Sleep, using this model. Underpinning this model is the concept that each role is necessary but not sufficient. We discuss the benefits fo pluralism in language and literacy pedagogy in an age of standards-based reforms and shifting repertoires of literacy practices in pedagogies that speak back to the Anthropocene.